Applying the Experience Effectiveness (XE) Framework in the Canadian Public Sector. Issue 1 (18th March 2019) - Langham, Jo'Anne; Paulsen, Neil
Abstract : Why is it so hard to interact with government services? The public sector has become citizen centered in designing and collaborating with the community to improve service. Even though governments invest in efforts to ensure public administration is aligned with the needs of the community, services still fail to meet the standards provided by equivalent private‐sector organizations. Citizen experiences fall short of expectations due to inadequate performance evaluation for the delivery of integrated and well‐designed services. Public‐sector performance measures must assess and include the impact that services have on citizens. This article describes the extension and further development of the Experience Effectiveness (XE) Measurement Framework. If properly utilized, public‐sector organizations can implement the framework to evaluate the effectiveness of citizen experiences based on human‐centered, universal, and systems‐thinking heuristics. Through a multiphase mixed‐method design, we test the XE Framework and its operational development with two projects in the Innovation Lab for the Canadian Department of Innovation, Science and Economic Development. The case studies demonstrate that the XE Framework clearly differentiates the quality of the experience and identifies areas for improvement. Results also indicate that the bureaucracy distorted the creation and delivery of the service citizens received. Organizational culture, climate, structures, and values significantly shape the outcome and provision of government services, which raises further questions about design and innovation in public administration and the role of accountability.